A homozygous KASH5 frameshift mutation causes diminished ovarian reserve, recurrent miscarriage, and non-obstructive azoospermia in humans - Hou, Xiaoning; Zeb, Aurang; Dil, Sobia; Zhou, Jianteng; Zhang, Huan; Shi, Baolu; Muhammad, Zubair; Khan, Ihsan; Zaman, Qamar; Shah, Wasim Akbar; Jiang, Xiaohua; Wu, Limin; et al. (Frontiers in Endocrinology, 2023)
The meiosis-specific LINC complex, composed of the KASH5 and SUN1 proteins, tethers the moving chromosomes to the nuclear envelope to facilitate homolog pairing and is essential for gametogenesis. Here, we applied whole-exome sequencing for a consanguineous family with five siblings suffering from infertility, and identified a homozygous frameshift mutation in KASH5 (c.1270_1273del, p. Arg424Thrfs*20). This mutation leads to the absence of KASH5 protein expression in testes and non-obstructive azoospermia (NOA) due to meiotic arrest before the pachytene stage in the affected brother. The four sisters displayed diminished ovarian reserve (DOR), with one sister never being pregnant but still having dominant follicle at 35 years old and three sisters suffering from at least 3 miscarriages occurring within the third month of gestation. The truncated KASH5 mutant protein, when expressed in cultured cells, displays a similar localization encircling the nucleus and a weakened interaction with SUN1, as compared with the full-length KASH5 proteins, which provides a potential explanation for the phenotypes in the affected females. This study reported sexual dimorphism for influence of the KASH5 mutation on human germ cell development, and extends the clinical manifestations associated with KASH5 mutations, providing genetic basis for the molecular diagnosis of NOA, DOR, and recurrent miscarriage.